DO REGULATION, MAQASID SHARIAH AND INSTITUTIONAL PARAMETER IMPROVE ISLAMIC BANK EFFICIENCY? - Wan Hakimah Wan Ibrahim; Abdul Ghafar Ismail (Bank Indonesia, 2020)
We use a new dataset on Islamic banks to link regulation and bank efficiency. Specifically, we examine how bank efficiency is influenced by: (i) bank regulation, (ii) institutional variables, (iii) economic freedom, and (iv) Shariah law parameters. Our hypothesis attempts to prove that better regulation will produce a higher level of efficiency. We will also try to prove that the Shariah law parameter will promote better efficiency among Islamic banks. Data Envelopment Analysis (DEA) is used to measure efficiency, while the panel data method is used to analyse the data. Specifically, our results suggest that a significant relationship exists between bank efficiency and greater restrictions on Islamic bank activities. The results also show that regulatory quality has a positive and significant impact on bank efficiency. The negative coefficient of the economic freedom indicates that Islamic banks have a greater ability to enter into the banking industry and obtain an easy licence, create products and services, and close the business. All would dampen bank efficiency. Overall, our findings support the argument that regulation should be adapted to the risk and size level of the Islamic banks that are being regulated.